Making and learning: Envisioning a third place for Lakota artists. Issue 1 (2nd January 2022) - Tofte, Elizabeth; Stewart, Derek A.; Martel, Jennifer A.
ABSTRACT: This case study discusses a course where 125 South Dakota State University School of Design (SoD) students collaborated with faculty, staff, and 30 artists at Sitting Bull College (SBC), Standing Rock Sioux Reservation, North Dakota, US. Students received authentic instruction through SBC artist workshops, conversations, and storytelling, then joined visioning exercises to design festival grounds, workshop spaces, kitchen and dining facilities, and guest camping. Students demonstrated that they understood the function of a "third place" by asking informed questions, reflecting on unique cultural requirements, and looking to the future to supply sustainable site and building recommendations. All interactions were held online. Students' reflections were gathered using Brookfield's Critical Incident Questionnaire. Tara Page's embodied and material pedagogies are useful when making, designing, and learning about sites, local culture, and people. Future work will examine how knowledge, understanding, learning, and belonging strengthen the placemaking process to better prepare students for professional practice.